Tinjauan Yuridis Cash Waqf Linked Ṣukūk (CWLS): Sebagai Alternatif Wakaf Produktif - abbas sofwan matlail fajar; Fiqih Nurhasyim (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
This research discusses cash waqf and Cash Waqf Linked Sukuk (CWLS) in Indonesia. Cash waqf is a waqf instrument that uses money as a commodity, managed by the Islamic Financial Institution Receiving Cash Waqf (LKS-PWU) and the Indonesian Waqf Board (BWI). CWLS is a cash waqf instrument used to purchase government-issued Sukuk, making it a productive waqf alternative.This study aims to explain the legal status of cash waqf in Islamic law and the problems found. The results show that the legal status of cash waqf has differing opinions among scholars. Some scholars allow cash waqf with certain conditions, such as being used as business capital.The research method used is normative with a legislative approach. This research can provide literacy on the legal status of cash waqf and the mechanism of CWLS as a productive effort. CWLS can be a productive and beneficial waqf alternative for the community, increasing the potential of cash waqf in Indonesia. Thus, this research is expected to contribute to the development of cash waqf in Indonesia.